Precision Water Irrigation System for Agriculture using IoT Framework - Gaurav Kumar (International Journal of Modern Agriculture, 2021)
The precision agricultural irrigation System has an important impact in overcoming all current challenges in the agricultural sector by replacing the traditional methods of doing agricultural features in a very specific way to help farmers monitor and remotely manage their farms. There are several existing systems integrating the Internet of Things (IoT) for agricultural operations and decreasing the greenhouse effect, but then there is an increasing need to minimize the greenhouse effect for IoT itself, so that people might deploy Green Internet of Things in agriculture, that will help to conserve energy and allow better use of agricultural resources. The call for more food will increase in order to accommodate the growing population, and new strategies should be designed to create more reliable strategies for agricultural production. With the smarter water management point on productivity and rational use of environmental assets, there is a requirement to form novel farming methods. Taking into consideration the requirement to gather novel records regarding the rural cycles, that is the case of opportunities that occur at the crops throughout its life cycle, community of scientists began discovering a fresh era which could be applicable to meet the needs of Accurate Agriculture. Continuous research into low-cost, smaller, extra-energy-green community nodes will result in the need for IoT. One of the distinctive uses of computer systems in farming is watering irrigation control.